A study on willingness in attendding training among staff: A case study at University Malaysia Kelantan / Nur Auni Mohamad Yusof - Mohamad Yusof, Nur Auni (2011)
There are numerous factors that influence the participation in attending training among staff. These factors are constantly individual characteristic, social support and perceived training. This study then was conducted to identify the factor that influencing participation in attending training among staff and to assess relationship between factors and participation in attending training. The research in this study is based on questionnaire distributed to the 100 respondents who were staff in University Malaysia Kelantan. The data collected was then tested on its reliability, and then further analyzed using frequency analysis, and Pearson Correlation Coefficient. Besides, Regression Analysis was used to test the hypotheses in this study. The findings of this paper suggest that only two factors are significant factors in explaining participation in attending training among staff at UMK which is individual characteristic and perceived benefits. Based from the results obtained in this study, the researcher suggests some recommendations that can help UMK to improve in training program